Protection against Doxorubicin-Induced Cardiotoxicity through Modulating iNOS/ARG 2 Balance by Electroacupuncture at PC6. (22nd March 2021) - Wang, Jingya; Yao, Lin; Wu, Xiaoli; Guo, Qi; Sun, Shengxuan; Li, Jie; Shi, Guoqi; Caldwell, Ruth B.; Caldwell, R. William; Chen, Yongjun
Abstract : Background . Doxorubicin (DOX) is a commonly used chemotherapeutic drug but is limited in clinical applications by its cardiotoxicity. Neiguan acupoint (PC6) is a well-recognized acupoint for the treatment of cardiothoracic disease. However, whether acupuncture at PC6 could be effective in preventing DOX-induced cardiotoxicity is still unknown. Methods . A set of experiments were performed with myocardial cells, wild type, inducible nitric oxide synthase knockout (iNOS-/-), and myocardial-specific ablation arginase 2 (Myh6-ARG 2-/-) mice. We investigated the protective effect and the underlying mechanisms for electroacupuncture (EA) against DOX-induced cardiotoxicity by echocardiography, immunostaining, biochemical analysis, and molecular biotechnology in vivo and in vitro analysis. Results . We found that DOX-mediated nitric oxide (NO) production was positively correlated with the iNOS level but has a negative correlation with the arginase 2 (ARG 2) level in both myocardial cells and tissues. Meanwhile, EA at PC6 alleviated cardiac dysfunction and cardiac hypertrophy in DOX-treated mice. EA at PC6 blocked the upregulation of NO production in accompanied with the downregulated iNOS and upregulated ARG 2 levels in myocardial tissue induced by DOX. Furthermore, knockout iNOS prevented cardiotoxicity and EA treatment did not cause the further improvement of cardiac function in iNOS-/- mice treated by DOX. In contrast, deficiency of myocardial ARG 2 aggravated DOX-induced cardiotoxicity and reduced EA protective effect. Conclusion . These results suggest that EA treatment at PC6 can prevent DOX-induced cardiotoxicity through modulating NO production by modulating the iNOS/ARG 2 balance in myocardial cells.